2016
DOI: 10.3390/su8050418
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Tourism and Food Culture

Abstract: Abstract:In recent years, gastronomy has established itself as one of the key elements for the enhancement, sustainable and consolidation of tourist destinations. The aim of this paper is to contribute to the advancement of knowledge on gastronomic tourism in European countries, specifically in the analysis of the relationship between gastronomy, culture and tourism as the research focuses on the city of Córdoba, Spain. The methodology of this research involved conducting surveys with foreign travelers who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 36 publications
1
55
0
2
Order By: Relevance
“…Food and beverage is one of the most important factors in the tourism industry [64,70,71] as it attracts tourists to enjoy new tastes of cuisine [72]. With the gastronomy, among the intangible cultural values of the destination, tourists can enjoy the local specialties and explore and perceive the authentic cultural identity of the local people [73][74][75][76].…”
Section: Food and Beveragementioning
confidence: 99%
“…Food and beverage is one of the most important factors in the tourism industry [64,70,71] as it attracts tourists to enjoy new tastes of cuisine [72]. With the gastronomy, among the intangible cultural values of the destination, tourists can enjoy the local specialties and explore and perceive the authentic cultural identity of the local people [73][74][75][76].…”
Section: Food and Beveragementioning
confidence: 99%
“…With reference to the role of consumers, during a scan of contributions, it emerged that the positive outcomes of partnerships among operators from various industries [12,60] can greatly improve customers' satisfaction and the quality of services for tourists, such as with respect to the oleotourist's experience [61,62]. Furthermore, Tudisca et al [63] debated about the participation of tourists and other actors in the activities that farmers carried out; consequently, the roles cannot be considered static as they change along with the proposal of new activities.…”
Section: Oleotourismmentioning
confidence: 99%
“…Such characteristics are present in at least 16 countries bordering the Mediterranean Sea. Their diets slightly vary depending on the cultures of each country but, in general, they are within a framework of ethnic origin and traditional agricultural production that generates the consumption of local fruits and vegetables, cereals, potatoes, legumes, nuts and seeds, olive oil, fish, poultry, small amounts of red meat, eggs, and wine in moderate amounts (Jiménez-Beltrán, López-Guzmán, & Santa Cruz, 2016). Some research has shown that food culture has a direct influence on consumer buying behavior.…”
Section: Culture and Food Consumptionmentioning
confidence: 99%